Human immunodeficiency virus infection in a child revealed by a massive purulent pericarditis mistaken for a liver abscess due to Staphylococcus aureus - Ngo Nonga Bernadette; N Kamgaing; F Monebenimp; C Simeu (Wolters Kluwer Medknow Publications, 2015)
Massive purulent andacute pericarditis in children is a life-threatening disease associated with high mortality. It has been described tocomplicate usuallya bronchopulmonary infectionbut is currently uncommon in the era of antibiotics. Acute and massive purulent pericarditis has been rarely reported in children in association with human immunodeficiency virus (HIV) infection. This is a case of a10-year-old boy who presented with signs of sepsis and cardiac tamponade due to a massive staphylococcal purulent pericarditis complicating an unknown HIV infection.The child underwent pericardiectomy, intensive treatment, and survived this life-threatening disease.